Policy Innovation to Support City Food Security - Mediatrix, Yuliana Maria; Prasetyo, Pius Sugeng (KnE Social Sciences, 2022)
Food security has become a global issue and has raised concerns for both government and non-government parties. Gaps in meeting food needs are often found in various parts of the world. On the one hand, we find people who die of hunger due to limited access to food, but on the other hand, we find people who have too much food. The United Nations has included food issues as part of its global agenda (Sustainable Development Goal #2: Zero Hunger). This confirms the seriousness of problems related to food. The Indonesian Government continues to strive to promote the strength of its food sector through various policy innovations. The food estate launched by the Government basically seeks to create food centers in several regions with the hope of encouraging increased production to be able to meet the food needs of the community. Innovation is also carried out at the city level with Government policies and support from the non-governmental sector to create urban farming. One example is a program carried out in the city of Bandung and which has spread throughout other sub-districts and urban villages (kelurahan). Urban farming, which is given the name Buruan Sae, is a movement to supplement city food, and it is mostly carried out by communities or community groups and is adapted based on local cultural conditions and practices. The urban farming system can provide economic, social, health, environmental and educational benefits. This was qualitative research and data were collected through a literature review and in-depth interviews. This paper found that this innovation in the food policy system can encourage the production side to meet food needs, thereby promoting the sustainability of the food system in urban areas. Keywords: food security, innovation, food estate, urban farming, sustainability